Early versus late dressing removal in clean and contaminated midline laparotomy wounds: a non-randomized pilot study - C., Vijayakumar; R., Prabhu; V., Muthukrishnan; R., Kalaiarasi; T., Swetha (International Surgery Journal, 2018)
Background: This study was carried out to evaluate the efficacy of early versus late dressing removal in clean and contaminated midline laparotomy wounds. Methods: Fifty patients aged ≥18 years who were admitted and operated for surgical procedures (both emergency and elective) were included in the study. All laparotomy wounds had fulfilled the CDC criteria. Twenty-five patients each were included in early dressing removal group and the late removal group. In early removal group, the laparotomy wound dressing was removed within 48 hours and in late removal group, was removed after 48 hours of surgery. The incidences of superficial and deep surgical site infection (SSI) in both groups were analysed. Other secondary parameters like incidence of wound dehiscence and secondary suturing were also analysed. Results: Twenty-five patients each, in early removal group and in late removal group were included for final analysis. The incidence of superficial SSI (%) was significantly less in early removal group (65.50 versus 89.50; p= <0.001). The duration (days) required for complete wound healing (8.52 versus 10.65; p=0.734) was significantly less in the early removal group. The length of postoperative hospital stay (days) was significantly less in early removal group (10.30 versus 14.90; p= <0.001). Conclusions: Early removal of dressing significantly reduces the incidence of superficial SSI in midline clean and contaminated laparotomy wounds. It also significantly reduces the duration required for complete wound healing and facilitates early discharge of the patient compared to late dressing removal.